Pendampingan Penyusunan Laporan Keuangan BUMNag Saiyo Sakato Nagari Gurun Menggunakan Microsoft Excel Sederhana - Sri Adella Fitri; Atika Mayangsari Yozu (Asosiasi Dosen Pengabdian kepada Masyarakat Indonesia, 2022)
BUMNag Saiyo Sakato Nagari Gurun which has the obligation to present financial statement transparency as a from of accountability has not recorded in detail and is not in accordance with applicable accounting standards, namely Financial Accounting Standards for Entities Without Public Accountability (SAK-ETAP). This service aims to improve the understanding and skills of managers in compiling the financial reports of BUMNag Saiyo Sakato based on SAK-ETAP. The method used is mentoring with a participatory approach from the manager starting from the initial survey, and Focus Group Discussion (FGD), followed by the delivery of material and then direct practice accompanied by the Team. The results of this study contribute to and increase the understanding and capacity of BUMNag Managers in recording transactions up to the BUMNag financial reporting stage.